2011
DOI: 10.1016/j.jpor.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the major connector in a maxillary denture on phonetic function

Abstract: It was indicated that the middle type of the major connector would be recommended from a viewpoint of phonetic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
2
16
1
Order By: Relevance
“…Therefore, even if it was wide, a connector located in the middle area of the palate was suggested to have less influence on speech production than connectors located in other areas [31]. The connector in this location induced only a slight disturbance in the articulation of consonants at the posterior areas of the palate, regardless of width or cross-sectional shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, even if it was wide, a connector located in the middle area of the palate was suggested to have less influence on speech production than connectors located in other areas [31]. The connector in this location induced only a slight disturbance in the articulation of consonants at the posterior areas of the palate, regardless of width or cross-sectional shape.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this evaluation can be conducted immediately using only a laptop computer with specific software and a headset microphone. With this system, we tried to analyze the influences of the incisal overjet [29] and palatal contour [30] of a maxillary complete denture on alveolar consonants as well as the influence of the position of the major connector in a maxillary removable partial denture on several consonants, in addition to the alveolar consonants [31]. In particular, we found that locating the major connector in the middle area of the palate results in a smaller disturbance than in other areas from the viewpoints of accuracy of phonetic output, a shorter duration of consonants, and the tendency to change to other consonants.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that, speech problem was improved or restored to normal when tissue coverage by the MCwas decreased, such as with a PB or PS [45,68]. Wada et al,( 2011Wada et al,( , 2014 investigated the effect of width and cross-sectional shape of MMCs on the accuracy of speech production. The experimental connectors were fabricated to simulate bars (narrow, 8-mm width) and plates (wide, 20-mm width).…”
Section: Patient Comfort and Satisfaction: MC Design Does Influencementioning
confidence: 99%
“…The experimental connectors were fabricated to simulate bars (narrow, 8-mm width) and plates (wide, 20-mm width). Two types of cross-sectional shapes in the sagittal plane were specified: flat and plump edge and concluded that, the width and cross-sectional shape of the connectors had limited effects on the articulation of consonants at the palate [69,70]. Also, they evaluated the influence of the major connectors on phonetic function with six test sounds using a speech recognition system.…”
Section: Patient Comfort and Satisfaction: MC Design Does Influencementioning
confidence: 99%
See 1 more Smart Citation